Assessment of the pollution status of the coastal waters of Kotabunan Village, East Bolaang Mongondow Regency (North Sulawesi Province, Indonesia) using the pollution index (IP) - Asthisa, Dias; Valina, Rahmi; Musada, Zulkarnain; Ilahude, Satrio; Lesi, Inka (Universitas Sam Ratulangi, 2024)
This study aims to assess the pollution status of the coastal waters of Kotabunan Village, East Bolaang Mongondow Regency, North Sulawesi Province, Indonesia, using the pollution index (PI). The water quality parameters monitored include temperature, Total Dissolved Solid (TDS), pH, Dissolved Oxygen (DO), and salinity. Analysis of water quality data was compared with class III water quality standards based on Government Regulation Number 22 of 2021. The results of the water quality analysis showed that the temperature ranged from 28.4 - 31.5 0C, TDS ranged from 2100 - 3120 mg/L, pH ranged from 7.93 - 8.24, DO ranged from 2.8 - 6.2 mg/L, and salinity ranged from 18.5 - 34 ppt. Based on these facts, the pollution index of these waters is 2.4 - 6.2 which indicates a light-moderate pollution status.